Narkomania w wojsku – wybrane uwarunkowania - Dudek, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2009)
Drug abuse is a growing social problem in Poland and is a particularly serious problem in the Military. The conditions of military service may be a factor that stimulates drug addiction among soldiers, particularly those who are psychically and physically weak and not adapted to team work. The psychical stress that results from the abrupt breaking of existing bonds and social relationships (family, colleagues, partners) is intensified by spatial limits (military barracks), and the character of military units (personal freedom limitation). Another important aspect is, natural in this situation, access to weapons and the nature of tasks performed by a modern army. Yet the army continues to recruit young people who are physically and mentally weaker and weaker. In face of this problem, the commanders, supervisors and teachers are required to possess not only psychological and pedagogical knowledge, but also ethical and moral awareness. The article is based on empirical results of the test conducted in 2007 among 100 conscription soldiers of the Lublin Garrison of the Polish Army.